Orçamento Participativo de Fortaleza: uma promessa a ser cumprida - Moreira, Helon Bezerra (2015)
This paper brings a reflection on the nature and democratic character of the Collaborative Budgeting experience in the city of Fortaleza between the years 2005 and 2014. A public policy of collaborative administration, characterized by the perspective of articulation between democracies of the participative and representative sorts. A systematic accompaniment of this policy through an investigative effort – initiated in the first decade of the year 2000, in the social science scope – unveils defining features of liberal democracy to limit the collaborative potential of this experience, which raises a central question about the actual manifestation of collaborative democracy at the context in study. The Collaborative Budgeting in Fortaleza began in 2005, during the first term of Luizianne Lins, a mayor affiliated to the PT party. Its continuity until the first half of 2014, during the second year of the following mayor, Roberto Cláudio, which is affiliated to the PROS party, continues enigmatic. This work investigates the effective participation of the specific public – related to local public policies –, the percentage of the municipal budget that is in fact discussed and deliberated by the population, and the continuity of this experience with the shift of municipal administration, among other phenomena. For such task, this paper rescues conceptions and democratic theories of contemporaneous analysts, such as Santos (2001, 2003, 2006, 2007, 2010, 2012 and 2013) Coutinho (1979, 1988, 1989, 1994 and 2008) and Wood (1998, 2007, 2011 and 2014). The public policy in question is assessed through an experimental methodological approach that articulates several methodological principles found in the works of Silva e Silva (2008), Guba & Lincoln (2011), Lejano (2012) and Rodrigues (2008, 2011). The field research is completed by interviews with participants and politics coordinators. There are also studies with statistical and documental outlines on Fortaleza’s Collaborative Budgeting involved in the research.